2016
DOI: 10.1111/ejn.13263
|View full text |Cite
|
Sign up to set email alerts
|

Does surprise enhancement or repetition suppression explain visual mismatch negativity?

Abstract: A long tradition of electrophysiological studies, using oddball sequences, showed that the neural responses to a given stimulus differ when their presentation occurs frequently (standards) as compared to rare, infrequent presentations (deviants). This difference, originally described in acoustic perception, can also be detected in the visual modality and is termed as visual mismatch negativity (vMMN). Also, a large number of studies detected the reduction of the neuronal response after the repetition of a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…The later part of the response (~330ms in Figure 7B) appears to instead be generated from bilateral posterior sources. Our observations are congruent with expectation effects found over frontal electrodes in EEG (Feuerriegel et al, 2018;Hall et al, in press), and in BOLD signals in frontal areas such as inferior frontal and middle frontal gyri (Grotheer & Kovacs, 2015;Amado et al, 2016) and dorsolateral prefrontal cortex (den Ouden et al, 2009;Rahnev et al, 2011), as well as in ventral temporal regions when presenting face stimuli (e.g., Egner et al, 2010;Grotheer & Kovacs, 2015). Our results also provide further evidence that expectation effects underlying VMRs are not restricted to visual areas, as is commonly assumed in existing studies of visual mismatch responses.…”
Section: Stimulus Repetition Inhibits Expectation Effectssupporting
confidence: 92%
See 4 more Smart Citations
“…The later part of the response (~330ms in Figure 7B) appears to instead be generated from bilateral posterior sources. Our observations are congruent with expectation effects found over frontal electrodes in EEG (Feuerriegel et al, 2018;Hall et al, in press), and in BOLD signals in frontal areas such as inferior frontal and middle frontal gyri (Grotheer & Kovacs, 2015;Amado et al, 2016) and dorsolateral prefrontal cortex (den Ouden et al, 2009;Rahnev et al, 2011), as well as in ventral temporal regions when presenting face stimuli (e.g., Egner et al, 2010;Grotheer & Kovacs, 2015). Our results also provide further evidence that expectation effects underlying VMRs are not restricted to visual areas, as is commonly assumed in existing studies of visual mismatch responses.…”
Section: Stimulus Repetition Inhibits Expectation Effectssupporting
confidence: 92%
“…The finding that expectation effects in visual oddball designs are larger in the presence of stimulus change (i.e., for unrepeated stimuli), is consistent with a substantial body of evidence from non-oddball designs. Previous studies have shown that response differences to expected/surprising stimuli are larger for unrepeated compared to repeated stimuli (Amado et al, 2016;Waconge et al, 2011;Todorovic & de Lange, 2012;Kovacs et al, 2012;Larsson & Smith, 2012;Symonds et al,2016). That stimulus repetition appears to suppress expectation effects suggests that there are at least two interacting mechanisms which underlie visual oddball effects, similar to models proposed to account for auditory mismatch responses (Costa-Faidella, et al, 2011;Mittag et al, 2016).…”
Section: Stimulus Repetition Inhibits Expectation Effectsmentioning
confidence: 96%
See 3 more Smart Citations